(untitled) (diségno, 2021)
This contribution focuses on the visionary component of Carpiceci’s architectural composition. An ‘integral architect’ and a humanist, Alberto Carpiceci (1916-2007) graduated from the Faculty of Architecture in Rome in 1939. As a follower especially of Vincenzo Fasolo, whom he assisted for a while, Carpiceci learnt History and Stiles of Architecture, not only of the ancient Rome but of both Renaissance and Baroque, too. He focused not so much on decorative details but on the aspiration to the large-scale project, the magnificence, both monumental and celebrative components. This cultural background triggered his passion for Michelangelo and, above all, for Leonardo, one of the main topics of his research over his whole lifetime. Leonardo’s architectural drawings, which inspired many other visionary architects, such as Ètienne-Louis Boullée, were studied and redrawn by Carpiceci, becoming one of the keys to understanding his visionary architectures. Fantastic summaries of several influences being strayed throughout history were reworked by Carpiceci’s creative soul and constructive mind through the medium of the drawing, which has always been the nodal point of his work, not only concerning architecture but tout court.